Biomechanical Differences Exhibited During Sit-To-Stand Between Total Knee Arthroplasty Designs of Varying Radii - He Wang (2018)
The purpose of the study was to investigate the influence of the mechanical differences between a single-radius total knee arthroplasty (SR TKA) and a multi-radius (MR) TKA design on the functional performance during a sit-to-stand movement. Three-dimensional kinematics and electromyography for selected knee flexor and extensor muscles were obtained for 16 (8 SR and 8 MR) unilateral, posterior-stabilized TKA participants. Compared to the SR group, the MR group demonstrated compensatory adaptations, with increases in performance time, trunk flexion displacement and velocity, and knee extensor electromyography; and greater relative hamstring co-activation of the MR limbs was needed to increase joint stability. An initial knee abduction displacement was exhibited by more MR than SR participants. In conclusion, SR TKA provides functional benefits to patients. © 2006 Elsevier Inc. All rights reserved.